Objects of liberty : British women writers and revolutionary souvenirs - Buck, Pamela, 1975- (Newark : University of Delaware Press, 2024)
"Objects of Liberty explores the prevalence of souvenirs in British women's writing during the French Revolution and Napoleonic era. It argues that women writers employed the material and memorial object of the souvenir to circulate revolutionary ideas and engage in the masculine realm of political debate. While souvenir collecting was a standard practice of privileged men on the eighteenth-century Grand Tour, women began to partake in this endeavor as political events in France heightened interest in travel to the Continent. Looking at travel accounts by Helen Maria Williams, Mary Wollstonecraft, Catherine and Martha Wilmot, Charlotte Eaton, and Mary Shelley, this study reveals how they used souvenirs to affect political thought in Britain and contribute to conversations about individual and national identity. At a time when gendered beliefs precluded women from full citizenship, they used souvenirs to redefine themselves as legitimate political actors. Objects of Liberty is a story about the ways that women established political power and agency through material culture"--
Cover -- Series Page -- Title Page -- Copyright -- Dedication -- Contents -- List of Figures -- Acknowledgments -- Introduction -- 1. Helen Maria Williams's Sentimental Objects in Letters from France -- 2. Mary Wollstonecraft and Political Spectacle in An Historical and Moral View of the French Revolution -- 3. Imperial Collecting in Catherine and Martha Wilmot's Travel Journals -- 4. Charlotte Eaton's Battlefield Relics in Narrative of a Residence in Belgium -- Conclusion: Refiguring the Revolution in Mary Shelley's Rambles in Germany and Italy -- Notes -- Bibliography -- Index
JSTOR
Keywords: Travelers' writings, English -- History and criticism; English prose literature -- Women authors -- History and criticism; English prose literature -- 18th century -- History and criticism; English prose literature -- 19th century -- History and criticism; Literature and revolutions; English literature -- Political aspects; Écrits de voyageurs anglais -- Histoire et critique; Prose anglaise -- 18e siècle -- Histoire et critique; Prose anglaise -- 19e siècle -- Histoire et critique; Littérature et révolutions.; LITERARY CRITICISM / General; Electronic books